Tribological behavior of graphite oxide reinforced polyethersulfone composite under drying sliding condition. Issue 7 (20th September 2016) - Yan, Shicheng; Yang, Yulin; Song, Laizhou; Qi, Xiaowen; Xue, Yahong; Duan, Changsheng
Abstract : Nano‐sized graphite oxide (GO) sheets prepared from expanded graphite (EG) particles were incorporated into polyethersulfone (PES) to improve the friction and wear properties of this polymer. The influence of GO addition on the mechanical, thermal, and tribological performances of PES composites was evaluated. The results of Fourier transform infrared spectroscopy and scanning electron microscopy for GO/PES composites reveal that the hydrogen bonding interaction between GO sheets and PES matrix is formed. The mechanical and thermal properties of PES composites are obviously enhanced due to the incorporation of GO sheets. The friction reducing and anti‐wear properties of GO/PES composites are much better than those of the pure PES. Among these fabricated GO/PES composites, the PES composite reinforced with GO addition of 0.6 wt% exhibits the lowest friction coefficient (0.17) and specific wear rate (1.07 × 10 −14 m 3 /Nm). This can be attributed to the homogeneous dispersion of GO sheets within PES matrix and the strong interfacial interaction between them, as well as the existence of uniform PES transfer film on the frictional interface. POLYM. COMPOS., 39:2320–2335, 2018. © 2016 Society of Plastics Engineers